Physicochemical, Biological, and Antibacterial Properties of Four Bioactive Calcium Silicate-Based Cements - Yu-Ji Jang; Yu-Jin Kim; Huong Thu Vu; Jeong-Hui Park; Seong-Jin Shin; Khandmaa Dashnyam; Jonathan C. Knowles; Hae-Hyoung Lee; Soo-Kyung Jun; Mi-Ran Han; Joon-Haeng Lee; Jong-Soo Kim; et al. (MDPI AG, 2023)
Calcium silicate-based cement (CSC) is a pharmaceutical agent that is widely used in dentistry. This bioactive material is used for vital pulp treatment due to its excellent biocompatibility, sealing ability, and antibacterial activity. Its drawbacks include a long setting time and poor maneuverability. Hence, the clinical properties of CSC have recently been improved to decrease its setting time. Despite the widespread clinical usage of CSC, there is no research comparing recently developed CSCs. Therefore, the purpose of this study is to compare the physicochemical, biological, and antibacterial properties of four commercial CSCs: two powder-liquid mix types (RetroMTA® [RETM]; Endocem® MTA Zr [ECZR]) and two premixed types (Well-Root™ PT [WRPT]; Endocem® MTA premixed [ECPR]). Each sample was prepared using circular Teflon molds, and tests were conducted after 24 h of setting. The premixed CSCs exhibited a more uniform and less rough surface, higher flowability, and lower film thickness than the powder-liquid mix CSCs. In the pH test, all CSCs showed values between 11.5 and 12.5. In the biological test, cells exposed to ECZR at a concentration of 25% showed greater cell viability, but none of the samples showed a significant difference at low concentration (p > 0.05). Alkaline phosphatase staining revealed that cells exposed to ECZR underwent more odontoblast differentiation than the cells exposed to the other materials; however, no significant difference was observed at a concentration of 12.5% (p > 0.05). In the antibacterial test, the premixed CSCs showed better results than the powder-liquid mix CSCs, and ECPR yielded the best results, followed by WRPT. In conclusion, the premixed CSCs showed improved physical properties, and of the premixed types, ECPR exhibited the highest antibacterial properties. For biological properties, none of these materials showed significant differences at 12.5% dilution. Therefore, ECPR may be a promising material with high antibacterial activity among the four CSCs, but further investigation is needed for clinical situations.